PENGARUH PROFITABILITAS, FREE CASH FLOW, PERTUMBUHAN PENJUALAN, UKURAN PERUSAHAAN TERHADAP KEBIJAKAN HUTANG - Zuhria, Siti Fatimatul; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This study aimed to analyze and examine the effect of profitability, free cash flow, sales growth and size of thecompany debt policy. The population in this study are firms Food and Beverages in the Indonesia StockExchange. The sampling technique used purposive sampling, data collection techniques using documentationtechnique derived from the annual report. Analysis of data using multiple linear regression analysis. The resultsof this study indicate that profitability has a negative impact, which means companies with a high rate of returnthat allows the company to finance the majority of internal funding, free cash flow has a negative relationshipmeans with their free cash flow that is higher by a manager can be used to pay debt , to distribute dividends toshareholders, and to finance the companys operations and can be reinvested, sales growth has a negativeimpact, which means that companies that have a high acceptance, it means having the ability of internal fundingis high, while the size of the company has a positive effect means that the size of the company which likely meanscompanies have more stable cash flow, the lower the risk of defaults, and have easy access to creditKeywords: profitability, free cash flow, sales growth, firm size, debt policy.